Repurposing of statins for Buruli Ulcer treatment: antimicrobial activity against Mycobacterium ulcerans - Dominguez, Juan; Mendes, Ana I.; Pacheco, Ana R.; Peixoto, Maria J.; Pedrosa, Jorge; Fraga, Alexandra G. (Frontiers in Microbiology, 2023)
Mycobacterium ulcerans causes Buruli Ulcer, a neglected infectious skin disease that typically progresses from an early non-ulcerative lesion to an ulcer with undermined edges. If not promptly treated, these lesions can lead to severe disfigurement and disability. The standard antibiotic regimen for Buruli Ulcer treatment has been oral rifampicin combined with intramuscular streptomycin administered daily for 8 weeks. However, there has been a recent shift toward replacing streptomycin with oral clarithromycin. Despite the advantages of this antibiotic regimen, it is limited by low compliance, associated side effects, and refractory efficacy for severe ulcerative lesions. Therefore, new drug candidates with a safer pharmacological spectrum and easier mode of administration are needed. Statins are lipid-lowering drugs broadly used for dyslipidemia treatment but have also been reported to have several pleiotropic effects, including antimicrobial activity against fungi, parasites, and bacteria. In the present study, we tested the susceptibility of M. ulcerans to several statins, namely atorvastatin, simvastatin, lovastatin and fluvastatin. Using broth microdilution assays and cultures of M. ulcerans-infected macrophages, we found that atorvastatin, simvastatin and fluvastatin had antimicrobial activity against M. ulcerans. Furthermore, when using the in vitro checkerboard assay, the combinatory additive effect of atorvastatin and fluvastatin with the standard antibiotics used for Buruli Ulcer treatment highlighted the potential of statins as adjuvant drugs. In conclusion, statins hold promise as potential treatment options for Buruli Ulcer. Further studies are necessary to validate their effectiveness and understand the mechanism of action of statins against M. ulcerans.